A Novel Approach on Micro Sponges Drug Delivery System: Method of Preparations, Application, and its Future Prospective - Mandal, Suraj; Bhumika, Km.; Kumar, Mukesh; Hak, Jiyaul; Vishvakarma, Prabhakar; Sharma, Umesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Microsponges are porous microspheres ranging in size from 5 to 300 micrometers used in a polymeric delivery system. They have been studied for biomedical applications, including targeted medicine delivery, transdermal drug delivery, anticancer drug delivery, and bone substitutes. This research aims to conduct a detailed examination of existing trends and future prospects for a microsponge-based medicine delivery system. The current study investigates the Microsponge Delivery System's design, operation, and possible therapeutic uses (MDS). The therapeutic potential of microsponge-based formulations, as well as patent data, were thoroughly investigated. The authors discuss several efficient methods for producing microsponges, including liquid-liquid suspension polymerization, quasi-emulsion solvent diffusion, water-in-oil-in-water (w/o/w) emulsion solvent diffusion, oil-in-oil emulsion solvent diffusion, the lyophilization method, the porogen addition method, the vibrating orifice aerosol generator method, the electrohydrodynamic atomization method, and the ultrasound-assisted microsponge. Microsponge may reduce undesired side effects and increase drug stability by boosting drug release. Hydrophilic and hydrophobic drugs can be loaded into a microsponge and transported to a specific target. When compared to traditional distribution methods, microsponge delivery technology offers numerous advantages. Microsponges, which are spherical, sponge-like nanoparticles with porous surfaces, can help increase drug stability. They efficiently alter drug release while also reducing adverse effects
Keywords: Microsponge; Microsponge delivery system; Novel drug delivery system; Quasi; emulsion solvent diffusion; Vibrating orifice aerosol generator; Electrohydrodynamic atomization